THE INTERPRETATION OF THE IMAGE OF OSIMA IN THE WORKS OF ABDUVALI QUTBIDDIN (European Journal of Interdisciplinary Research and Development, 2025)
In this article, the cycle of poems “Osima” by Abduvali Qutbiddin, a mature representative of contemporary literature, is subjected to analysis. The artistic-poetic, philosophical, and Sufi interpretations of the image of Osima are revealed. In addition, reflections are presented on the place and function of the image of Osima in the poet’s poetry.